Student Comfort With Medical Educational Modeling in Radiologic Technology Education. - Schmuck, Heather (Radiologic Science & Education, 2025)
Radiologic technology students must develop proficiency in patient positioning to achieve clinical competence, and many educational programs incorporate medical educational modeling (MEM) as a hands-on pedagogical approach to support this learning. This quantitative study, part of a larger research project, explored radiologic technology students' comfort levels with MEM across various roles and demographic factors. Using a validated survey instrument, data were collected from students enrolled in accredited baccalaureate-level programs. Overall, students reported high comfort levels with MEM; however, statistically significant differences emerged in specific contexts, particularly related to religious affiliation, age, and observer role experiences. These findings suggest that although MEM is generally well-received, educators should remain attentive to individual student experiences and demographic influences when designing and implementing MEM-based instruction. Reflective teaching practices that prioritize student comfort may enhance learning outcomes and foster more inclusive educational environments in radiologic technology programs.